Sustaining Adult Education And Social Change In Nigeria - C. Zuofa, Comfort (Advances in Social Sciences Research Journal, 2017)
Education is perceived as the most relevant tool or instrument for change, development and progress by all societies. Human history indicates that education remains the most important agent of social conservation and transformation. It is indeed the most significant means by which the experiences, the totality and cultural disposition of all human societies are transmitted from generation to generation. Essentially, the education system of a society evolved from within values, need and aspiration of such society. Adult education in this instance can be explained to mean educational programmes designed for individuals of various ages to enhance their abilities and potentials through diverse modes of formal, informal and non-formal education. This education is based on the peoples’ social, economic, political and cultural needs which further enhance their scope of adapting to societal immediate needs as well as facing future challenges. It is also a means of providing the adult individuals in the society opportunity to be equipped with relevant literacy skills required for their day to day activities. Invariably, adult education is a need- orientated and learner – centred field that has always been associated with social change. It is a revolutionary process that ensures the participation of most people in societal affairs. Social change cannot be achieved without reasonable and active involvement of the majority of the populace. With most emerging economies desperately seeking for social change in its entire ramification, adult education could be utilised as the main tool to achieving this desired change. Social change therefore refers to a total transformation of peoples’ orientation and living condition. This means that adult education needs to be reprogrammed in order to achieve that desirable change. Invariably, adult education should be such that can equip adult populace to participate and play vital roles in ensuring that the desired social change is achieved. However, researches from past studies have shown the existence of several situational, institutional and dispositional challenges to the effective implementation of adult education in emerging economies. Thus, the aim of this study was to identify challenges, appraise and determine how adult education can be sustained and enhance social change in emerging economies in Nigeria. To achieve this objective, the study adopted an exploratory qualitative research method. Views of key adult education stakeholders and practitioners in Nigeria were the study population for the study. Out of this population was drawn a sample of 540 stakeholders and practitioners using purposive sampling technique to respond to the interview which was the data collecting instrument. Validity and reliability were achieved by first assessing the plausibility in terms of already existing knowledge on some of the sustainability drivers for adult education, a leading emerging economy in Africa. The interviews were recorded and transcribed to create a data set of qualitative accounts. The findings revealed the successes of current adult education initiatives in achieving the goal of equipping Nigerian adults with literacy skills. Findings further indicated that the main philosophical consideration of this research was linked to the essential requirement of examining challenges of adult education in emerging economies for the purpose of capturing lessons aimed at enhancing more sustainable social change. They concluded by articulating genetic recommendations about best practice.